Sacred Ritual of Purification of Heirlooms, Nyangku - Muhammad Krisnawan; Deni Maulana Dipraja; Nurverawati Nurverawati; Nadhif Haj Pramanca; Hendrix Alamsyah; Shaila Shavika Rhadiva Crinata (Universitas Pendidikan Indonesia, 2022)
Nyangku was raised from the social issue of the Muslim community on the unfounded belief of the Maulid Nabi Muhammad SAW event, a traditional nyangku ceremony in Panjalu Village. The nyangku ceremony has the activity of washing heirlooms that are considered sacred, such as the keris weapon which is believed to be a hereditary relic of the guardians who spread Islam in Indonesia. The traditional nyangku ceremony makes the Muslim community confused because of the attachment of this ceremony to objects that can refer to the act of associating partners with Allah SWT. The nyangku ritual looks like glorifying the keris, the washing water of the keris is also taken by the residents because it is believed to have mystical powers to cure various diseases. In Islam, the law of abusing an object as a talisman (amulet) is haram and is an act of polytheism. The dispute over the meaning of the objectives in the Nyangku traditional ceremony has become a big question mark for the diverse Muslim community over the Nyangku traditional ceremony from Panjalu Village. Is it really an act of shirk and is preserved in the context of migusti or just as a tribute to the ancestors and is a form of cultural preservation in the context of mupusti? What are the views of people from the side who took part in carrying out the Nyangku custom and the views of figures who disagree with the Nyangku traditional ceremony which was held to coincide with the Birthday of the Prophet Muhammad SAW, in commemorating the birthday of the Prophet. A qualitative method with a descriptive approach was used in collecting all research data through observation, interviews, documentation and literature studies. This study found the existence of a community that still strongly maintains customs in the form of a purification ceremony for heirlooms called Nyangku. The findings of this study can serve as a reference for further research and for policy makers in relation to cultural preservation. The implications of this research are the main data in making a documentary film entitled Yanko.